2021
DOI: 10.3390/ijerph182413359
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CAD/CAM Ceramic Thickness on Shade Masking Ability of Discolored Teeth: In Vitro Study

Abstract: Shade matching is a common challenge that dentists face during fabrication of esthetic dental restoration. Thus, the aim of the current study was to assess the masking ability of two types of CAD/CAM ceramics for gaining high esthetic prosthesis. This in vitro study used a total sample size of 66 lithium disilicate (LD) and leucite reinforced (LR) CAD/CAM ceramics sub-grouped into three thicknesses: 0.5, 1, and 1.5 mm. Nine shades of natural dentin die materials were prepared as a replica of the underlying too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 45 publications
2
15
0
1
Order By: Relevance
“…Therefore, this finding supports the benefit of limiting the use of a 0.5 mm ceramic thickness in the fabrication of dental veneers for esthetic purposes only, while the use of a 1 mm thickness can be extended to the fabrication of inlays and onlays. The 1.5 mm thickness can be considered the optimum thickness for the fabrication of full-coverage restorations subjected to heavy masticatory loads [ 12 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, this finding supports the benefit of limiting the use of a 0.5 mm ceramic thickness in the fabrication of dental veneers for esthetic purposes only, while the use of a 1 mm thickness can be extended to the fabrication of inlays and onlays. The 1.5 mm thickness can be considered the optimum thickness for the fabrication of full-coverage restorations subjected to heavy masticatory loads [ 12 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the available CAD/CAM ceramics, lithium disilicate (LD), leucite-reinforced (LE) glass ceramics, and zirconia have proven to be the most favorable ceramic materials used in the oral cavity [ 8 , 9 , 10 ]. LD ceramic is considered the material of choice for the fabrication of posterior and anterior restorations because of its superior mechanical and esthetic properties [ 11 , 12 ]. Previous studies reported that LD ceramics showed comparable 5-year survival rates to those of zirconia when used for the fabrication of posterior crowns and fixed partial dentures [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Az évek múlásával a dentin színe egyre inkább a sötétebb sárgás, illetve szürkés árnyalatok irányába tolódik el a szekunder dentin képződése és a zománcréteg elvékonyodása miatt [18]. A kerámia rétegvastagsága is befolyásolja a végleges restaurátum színét: a vastagabb kerámiaréteg jobb fedőképességgel rendelkezik [5,8,9]. A fogzománc optikai tulajdonságainak fontos eleme a transzlucencia, amely reprodukálására a korszerű fogászati kerámiaanyagok alkalmasak [16,21].…”
Section: Bevezetésunclassified
“…Several recent studies evaluated the masking ability and shade reproduction of dental materials [ 26 , 27 , 28 , 29 , 30 ]. The studies investigated the properties of monolithic samples when placed over discolored substrates.…”
Section: Introductionmentioning
confidence: 99%